Intimate Partner Violence Among Persons With Mental Health-Related Disabilities in Canada - Brownridge, Douglas A. (Journal of interpersonal violence, 2022)
This study examined the elevated risk of intimate partner violence (IPV) among persons with mental health-related disabilities (MH-RD) and the extent to which known risk factors accounted for this phenomenon. Data were drawn from a nationally representative sample of 33,127 Canadians collected in 2014 as part of Statistics Canada’s General Social Survey. Results showed that respondents with MH-RD had more than three-fold increased odds of both overall and severe IPV victimization. Although females were more likely to possess a MH-RD, males and females with MH-RD reported similarly elevated odds of IPV victimization. Risk factors that contributed to a significant reduction in elevated odds of IPV for respondents with MH-RD were child maltreatment (CM), respondents’ nonprescription drug abuse, and perpetrators’ jealous, monitoring, and socially isolating behaviors. The inability to test additional risk factors and bidirectionality in the relationship between MH-RD and IPV may have contributed to the failure to fully account for these respondents’ elevated odds of IPV. Future research is needed to understand the complex mechanisms contributing to the elevated risk of IPV and enhance prevention and intervention strategies for this underresearched and underserved vulnerable population.